Mastering Systems Strategic Crises to Prevent Business Crises - Vrečko Igor; Mulej, Matjaž (Naše gospodarstvo/Our economy, 2012)
This paper deals with the problem of identifying and resolving strategic crises in business systems. Identifying strategic crises, based on the existing definitions of these crises, is often a matter of subjective interpretation, making it difficult to design and implement the necessary measures to resolve them. In this paper we define a new intellectual basis for the definition of strategic crisis and introduce the concept of a systemic strategic crisis. These are explained and defined as the cause of business strategic crises and the resulting operational crises. By defining the systemic strategic crises, we create the basis for introducing a holistic approach to solving strategic crises with the integration of strategic and project management acting on the concepts of systems thinking and creativity, which is briefly outlined in the proposed two-dimensional model of managing systems strategic crisis.